Effect of rainfall and temperature distribution on incidence of American bollworm on cotton in Haryana (MAUSAM, 2004)
The effect of rainfall and temperature distribution on the incidence of American bollworm on cotton in Haryana state has been studied. Higher rainfall coupled with moderate temperature from early vegetative stage till the early reproductive stage has been found to favour the incidence of the pest during the later stages of the crop. The weather conditions were nearly the same during the later stages (when the infestation is maximum) indicating that the distribution of rainfall and temperature during the early stages determines the infestation.